Comparative study of mini tomatoes varieties(lycopersicon esculentum.mill) in the greenhouse (Mongolian Journal of Agricultural Sciences, 2018)
In last few years, the size and amount of vegetable production is increasing on the demand market growth and consumer’s interest for small scaled or industrial farming. Therefore there is essential to develop and introduce the new technologies in vegetable production. In our specific climate condition, the class and green house production is very important, specially there is need to change the old varieties and introduce appropriate cultivars from countries with similar climate, which is suitable in cold winter. In this experiment had been studied a new varieties of mini tomato in Mongolian soil and climate condition. This experiment was aimed to test and compare by the length of growth period and mini tomato varieties as using the Mongolian variety Visniiviidnii in greenhouse. To achieve our purpose the following studies have done; To test growth period length and to measure the some biometric parameters of Korean and Mongolian varieties. Next is to compare the yield for those tomato varieties. The results of the study on the growth of mini tomatoes varieties showed that on the 11-th of April the plant was planted in a warm greenhouse, after of 41-45 days transplanted seedling with 5-6 leaves and 36-40 cm high in on May 28, therefore total growth period has continued from germination to harvest period for Vishnevidny (test variety) -169 days, in Black Joy-168 days, while other nine varieties was the growth of 165-166 days. The growth period was estimated from germination occurrence. The varieties height of main stem was for KT Orange (188 cm), KT Yellow TY (183 cm), KT Red (180 cm), Seminis SV7160 TC (180 cm), TY candy (180 cm), Yellow Galaxy (180 cm) which was added by 25-53 cm from control and 19-44 cm from other varieties. The average yield of per square meter was 3.2-9.6 kg for all varieties and followed by TY Candy (10.8 kg), Seminis-SVTC8715 TY.Хүлэмжний нөхцөлд жижиг жимст лоолийн (lycopersicon esculentum.mill) сортуудыг харьцуулан судласан дүнХураангуй: БНСУ-аас ирүүлсэн жижиг жимст лоолийн сортуудыг нутагшсан сорттой харьцуулан судлаж, сортуудыг аж ахуй, биологи, морфологийн онцлогоор нь шалгаруулахад зорилгоор уг судалгааг хийсэн. Судалгааны үр дүнгээс харахад жижиг жимст лоолийн сортуудын нийт ургалтын хугацаа нь соёололтын жигдрэлтээс эцсийн хураалт хүртэл тооцоход 9 сортод 165-166 хоногт, 2 сортод 169 хоногт буюу 3 хоногоор оройтож байсан. Гол ишний өндрөөр KT Orange(188 см), KT Yellow TY(183 см),KT Red(180 см), Seminis SV7160 TC(180 см), TY candy(180 см), Yellow Galaxy(180 см) тус тус байсан нь хяналт сортоос 25-53 см-ээр, бусад сортоос 19-44 см-ээр тус тус өндөр байсан байна. Навчин дахь хлорофиллийн тоог хэмждэг SPAD meter 500 багажаар 10 хоног тутам хэмжилт хийсэн үр дүнгээс харахад 6-р сард бүх сортуудад навчны хлорофиллийн тоо 45.9-49.9 байсан бол 7-р сад буурч 38.4-47.3 болсон. Энэ үзүүлэлт нь фотосинтезийн эрчим болон ногоон массын өсөлт, азотын хангамжаас хамаардаг үзүүлэлт юм. Лоолийн сортуудын 1 м2 талбайгаас тооцсон үр жимсний дундаж ургацаар 3.2-9.6 кг байсан бөгөөд хяналтаас давсан ургацаар TY Candy (10.8 кг), Seminis-SVTC8715 TY (9.6 кг ) сортууд ургацаар тус тус удаалж байгаа нь математик үнэмшлийн магадлаар буюу 20.0-55.6%-иар ахиу ургацтай байгаагаар батлагдсан. Дээрхи 2 сорт нь ургалтын хугацаагаар хяналтаас 4 хоногоор эрт байгаа нь эхний жилийн сорилтоор шалгарч байгаа юм. Эндээс үзэхэд Солонгос улсаар ирүүлсэн сортууд нь Монгол орны хөрс, цаг уурын нөхцөлд ургах боломжтойг нотолж байна.Түлхүүр үг: Жижиг жимст лооль, хоовон, сорт судалгаа, өсөлт хөгжилт.